VD_FINDINFO Pron / 2012 / 37 vom 29. Februar 2012 - VD Tribunal cantonal (2012)
DÉCISION D'IRRECEVABILITÉ, INTÉRÊT JURIDIQUEPROCÉDURE CIVILE, DÉLAI DE RECOURS | 420 al. 2 CC, 489 CPC, 492 al. 2 CPC, 492 CPC